Digital health experiences reported in chronic disease management: An umbrella review of qualitative studies. (December 2022) - Taylor, Monica L; Thomas, Emma E; Vitangcol, Kathryn; Marx, Wolfgang; Campbell, Katrina L; Caffery, Liam J; Haydon, Helen M; Smith, Anthony C; Kelly, Jaimon T
Introduction: Digital health interventions can be useful for the management of chronic disease. The aim of this study was to draw out universal themes to understand how people with chronic conditions experience digital health services, programmes, and interventions, and consequently, better inform future digital health delivery. Methods: An umbrella review was conducted to identify qualitative systematic reviews reporting digital health experiences in chronic disease. Themes for each included review were independently extracted and appraised by two review authors. Data analysis was conducted using the Constant Comparative method. Results: Twenty-two systematic reviews containing 240 individual studies were selected for inclusion. Mental health was the most common condition ( n  = 5, 23%), followed by cancer ( n  = 4, 18%) or a combination of chronic diseases ( n  = 4, 18%). Common themes across the conditions were categorised under nine headings, including: (i) participation and engagement (strong usability and engagement vs reluctance to use digital health when these concepts are ignored), (ii) trust, confidence, and competence (users felt reassured, however technology illiteracy led to a perceived lack of control), (iii) perceived value, perceived effectiveness, transaction cost (gained from efficient aspects of digital health, but also lost through the burden of keeping up with data entry), (iv) perceived care quality (requiring tailoring and fostering motivation), (v) barriers and threats (related to technology risks and challenges), (vi) health outcomes (improved self-management capability), (vii) relationships (improved participant-health professional interaction, but interpersonal aspects such as face-to-face contact were lacking), (viii) unplanned benefit (where digital health often led to users feeling more empowered in their health journey), and (ix) diversity of experiences (reflecting ambivalence of experiences and discipline-specific experiences). Conclusion: People with chronic conditions perceive digital health provides feelings of reassurance and the ability to self-manage their condition. While there is ambivalence across the participant experiences reported within the major themes, this umbrella review has outlined a need for future interventions that are user-friendly, flexible, and tailored to individual users. This will be best achieved through a co-design model, with the consumer actively involved in the planning and design of digital health products and services.